Non-linear externalities in firm locations: A computational estimation method - Giulio Bottazzi; Ugo M. Gragnollati; Fabio Vanni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
A stochastic discrete choice model and its related estimation method are presented which allow to disentangle non-linear externalities from the intrinsic features of the objects of choice and from the idiosyncratic preferences of agents. Having veried for the ergodicity of the underlying stochastic process, parameter estimates are obtained through numerical methods and so is their statistical signicance. In particular, optimization rests on successive parabolic interpolation. Finally, the model and its related estimation method are applied to the case of rm localization using Italian sectoral census data.
Keywords: C12; C13; C46; C52; R12; 330; Externalities; Heterogeneity; Computational methods; Firm localization